Analisis Efisiensi Teknis Tempat Pelelangan Ikan dan Strategi Pemberdayaan Pengelola Tempat Pelelangan ikan di Kabupaten Cilacap - Oke Setiarso; Neni Widayaningsih; Suharno Suharno (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
The objectives of this study is to analyze the level of empowerment management in the fish auction and KUD in Cilacap regency. This study is conducted with several approaches, namely technical efficiency analysis with the Data Envelopment Analysis (DEA), empowerment level analysis, SWOT analysis, and strategy for empowerment. Number of sample is 9 fish auctions (TPI) for efficiency analysis, 60 respondents for empowerment level analysis, and 30 respondents for strategic empowerment. The results are only one fish auction, TPI Pandanarang, has no efficient with 10.16 percents level ofefficiency; the management of TPI/KUD in Cilacap regency has a high level empowerment to improve and develop the welfare of fishermen, demonstrated with an average percentage of successfull is more than 50 percents in terms of the service to the fishermen, organization participation, and lobying ability with stakeholders; based on SWOT analysis, TPI Cilacap regency is located at hold and maintain so the empowerment strategy appropriate with the development of TPI is the market penetration and development of TPI/KUD. Keyword: technical efficiency, level of empowerment, empowerment strategy